Studi Pendahuluan: Strategi Promosi Kesehatan Mental Di Lingkungan Kampus Melalui Partisipasi Dosen Wali - Ni Gusti Made Rai; Tony Dwi Susanto; Eka Dian Savitri; Aurelius Ratu (JURNAL SOSIAL HUMANIORA (JSH), 2020)
In providing qualified, physically, and mentally health graduates, students' mental health should be paid more attention than before. As the mental-health affects a person's psychological condition, in this preliminary research, we seek to formulate the strategy in giving a framework for the PDC program. Academic advisors (dosen wali) became participants in this study. We consider them to know better what students need and can realize an effort to prevent mental health problems. The research used qualitative data and the FGD method to gain the data. The results indicated that how academic advisors need student mental health service as part of the academic process, which showed the crucial issues related to college student mental health.